Developments in consolidation and maintenance strategies in post-remission multiple myeloma. Issue 4 (2nd April 2020) - Morè, Sonia; Corvatta, Laura; Maracci, Laura; Costantini, Benedetta; Olivieri, Attilio; Offidani, Massimo
ABSTRACT: Introduction : Multiple Myeloma (MM) is a very heterogeneous clonal plasma cell hematological malignancy for which new therapies and transplantation effectively improve Progression-free survival (PFS) and overall survival (OS). Maintenance seems to have made a significant contribution in achieving these advances, whereas the real role of consolidation is still controversial. Despite lenalidomide having been approved as maintenance therapy after autologous stem cell transplantation (ASCT), the optimal maintenance agent, drug combinations, schedules, and duration are still under investigation. Areas covered : This review summarizes data regarding maintenance and consolidation therapies for transplant-eligible patients, updating on the ongoing developments in this area. Papers published on PubMed and abstracts presented at the ASCO, ASH, and EHA meetings up to December 2019 were used. Expert opinion : The available studies demonstrate that maintenance therapy is very effective although results from ongoing clinical trials suggest that disease features and minimal residual disease (MRD) status may optimize the selection of agents, schedule, and duration of maintenance therapy. Consolidation with last-generation drugs seems to be more effective and it could replace transplantation in some subgroups of patients.